A Study on the Model of College English Self-managed Learning Based on the Flipped Classroom - Yaqin Lu (Journal of Educational Issues, 2024)
With the rapid development of the information society, the traditional college English teaching model has become inadequate to meet the needs of social development. A new teaching model, the flipped classroom, has emerged. Based on blended learning theory and humanistic theory, this study focuses on the college English teaching model within the context of the flipped classroom, outlines the relationship between the flipped classroom and self-managed learning, analyzes the current situation of college students’ self-managed learning, and explores the construction of college English self-managed learning model. The experimental results indicate that the model of college English self-managed learning based on flipped classroom not only improves the quality of college English teaching and students’ self-managed learning abilities, but also has a positive impact on students’ attitudes toward study, which benefits the improvement of college students’ comprehensive abilities.